Construction and analysis of protein-protein interaction network associated with human sperm-egg interaction [electronic resource] - Soudabeh Sabetian Fard Jahromi, 1980- author (2015)
Thesis (Ph.D (Biosains)) - Universiti Teknologi Malaysia, 2015